2016
DOI: 10.1242/jcs.184309
|View full text |Cite
|
Sign up to set email alerts
|

Impaired mechanical response of an EDMD mutation leads to motility phenotypes that are repaired by loss of prenylation

Abstract: There are roughly 14 distinct heritable autosomal dominant diseases associated with mutations in lamins A/C, including Emery-Dreifuss muscular dystrophy (EDMD). The mechanical model proposes that the lamin mutations change the mechanical properties of muscle nuclei, leading to cell death and tissue deterioration. Here, we developed an experimental protocol that analyzes the effect of disease-linked lamin mutations on the response of nuclei to mechanical strain in living Caenorhabditis elegans. We found that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 60 publications
(65 reference statements)
3
48
0
Order By: Relevance
“…Interestingly, a recent study measured mechanical responses to external physical tension and found a significant increase in hypodermal nuclear stiffness in animals depleted for UNC-84 (Zuela et al 2016). Ectopic expression of LMN-1 carrying a L535P substitution, which mimics an Emery-Dreifuss muscular dystrophy mutation in the human LMNA gene, extends the effects of UNC-84 depletion on nuclear stiffness to include muscles (Zuela et al 2016).…”
Section: Mechanotransductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, a recent study measured mechanical responses to external physical tension and found a significant increase in hypodermal nuclear stiffness in animals depleted for UNC-84 (Zuela et al 2016). Ectopic expression of LMN-1 carrying a L535P substitution, which mimics an Emery-Dreifuss muscular dystrophy mutation in the human LMNA gene, extends the effects of UNC-84 depletion on nuclear stiffness to include muscles (Zuela et al 2016).…”
Section: Mechanotransductionmentioning
confidence: 99%
“…In an effort to understand the underlying mechanism of various laminopathies, a number of disease-related lamin mutations have been introduced into C. elegans. Many of these mutations disrupted C. elegans LMN-1 oligomerization in vitro and lamin function in vivo (Wiesel et al 2008;Bank et al 2011Bank et al , 2012Mattout et al 2011;Zuela et al 2016). For example, LMN-1DK46, which corresponds to the deletion of lysine 32 in the rod domain of lamin A/C in Emery-Dreifuss muscular dystrophy patients, causes defects in the lateral assembly of LMN-1 dimers and results in abnormal muscle structure and motility in the worm .…”
Section: Components Of the Nementioning
confidence: 99%
See 1 more Smart Citation
“…Restoring proper muscle nuclear response rescued disease phenotypes in these animals. 20 However, this hypothesis does not fully explain how a globally expressed mutation can have such a tissue specific effect, as not all muscle diseases caused by lamin mutations affect the exact same muscle sub-types. Furthermore, expressing the Y59C EDMD linked mutation did not affect muscle nuclear mechanical response, but rather the transcription of muscle specific developmentally expressed genes.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, expressing the Y59C EDMD linked mutation did not affect muscle nuclear mechanical response, but rather the transcription of muscle specific developmentally expressed genes. 20,21 Also, the skin, which is under constant mechanical tension, has no apparent phenotypes in this group of diseases. The many nuclear roles attributed to lamins are most likely mediated through their interactions with a variety of inner nuclear membrane proteins, which are differentially expressed within tissues.…”
Section: Introductionmentioning
confidence: 99%